REPRESENTATION OF THE HYBRIDITY OF JAVANESE WOMEN IN THE “TILIK” FILM - Dwi Ario Fajar (Premise: Journal of English Education and Applied Linguistics, 2022)
In the era of globalization, foreign and local cultures meet each other. The meeting caused some controversy regarding the existence of local culture and identity. Globalization will undoubtedly affect the position of the Javanese and their identity now. The Javanese now are hybrid Javanese who can take and accept and filter cultures outside of Javanese culture. Javanese women face more problems than Javanese men. Javanese women face patriarchal domination and the problem of Javanese women's identity in the era of globalization. The film "Tilik" is a short film that went viral during the Covid-19 pandemic. This film represents hybrid Javanese women present in the life of Javanese society today. The purpose of this study is to explain how Javanese women, like hybrid Javanese, can overcome all currents of globalization by absorbing, mixing, following, and modifying cultures outside Java without abandoning the noble values of Java. This research method uses descriptive qualitative with critical discourse analysis. The results show that Javanese women are hybrid women formed from various cultures and globalization but still adhere to Javanese cultural values in their daily lives.